Práticas de numeramento nos livros didáticos de matemática voltados para a educação de jovens e adultos - Paula Resende Adelino (2009)
This research examines how numeracy practices can be constituted and deployed in the Mathematics textbooks toward the Youth and Adults Education (EJA). We selected the book collection Living, Learning - Education for Youth and Adults - 2nd segment of Fundamental School of Global Publisher (specifically the books: Mathematics and Facts of Life, Volumes I and II) and focused our approach on rational numbers, by analyzing the exercises that seek to make students understand this set of numbers. In order to discuss the opportunities to set up numeracy practices beyond the identification of strategies that promote the acquisition of skills, we tried to establish a dialogue among authors that include reflections on literacy and numeracy, the ones who discuss the specificities of the relationship of male and female students (in the Education for Youth and Adults program) with mathematical knowledge and also those authors who contemplate the peculiarities of teaching rational numbers in basic education. In the analysis undertaken in this dissertation, we focused numeracy practices related to Communication through mathematics.